Spectrum of Cytopathological Causes of Cervical Lymphadenopathy- An Experience at Sahiwal Teaching Hospital - Raees Abbas Lail; Areeba Farooq; Qurrat-ul-Ain Tahir; Sadaf Shafique; Syeda Tooba Fatmi; Abdul Ghaffar (Journal of Aziz Fatimah Medical and Dental College)
ABSTRACT: